Pengaruh Air Rebusan Daun Sirsak Terhadap Penurunan Kadar Asam Urat pada Lansia Dengan Gout Arthritis - Niva Juliana; Siti Juwariyah; Mamat Supriyono (Lembaga Pengembangan Kinerja Dosen, 2023)
The older adults get, the greater the risk of someone getting gout. It is caused by a decrease in hormone levels when the hormone oestrogen decreases in the body; there is only a tiny amount of the hormone oestrogen, which helps remove uric acid through the urine and can cause the disposal of uric acid to become uncontrolled, resulting in a buildup of degenerative diseases, one of which is gout. One of the non-pharmacological actions that can be used to reduce uric acid levels is by giving soursop leaf boiled water. This study aims to determine the effect of soursop leaf-boiled water on reducing uric acid levels in the elderly before and after the intervention. This research method used quasi-pre- and post-testing in the intervention group. The sampling technique used was random sampling of 65 respondents using an observation sheet with SOP for soursop leaf stew. The analysis showed that the average uric acid level before giving soursop leaf decoction was 42.2%, with high uric acid levels. While the average high uric acid level after administration of soursop leaf-boiled water is 12.3% with moderate uric acid levels and as much as 87.7% with average or low uric acid levels, The results of the marginal homogeneity test obtained a P value of 0.001 (<0.05), meaning that there was a significant difference in mean between the pretest and post-test, which affected giving soursop leaf boiled water to reduce uric acid levels in the elderly—suggestions for health services to provide facilities to health service workers so they can apply traditional medicine.